2009
DOI: 10.3171/2009.4.peds08204
|View full text |Cite
|
Sign up to set email alerts
|

Experiences with a gravity-assisted valve in hydrocephalic children

Abstract: Object Over the past decade, a gravity-assisted valve (GAV) has become a standard device in many European pediatric hydrocephalus centers. Because past comparative clinical outcome studies on valve design have not included any GAV, the authors in this trial evaluated the early results of GAV applications in a pediatric population. Methods For a minimum of 2 years the authors monitored 169 of 182 hydrocep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…Twenty-two articles were included in the final evidentiary table. Reasons for exclusion of fulltext articles included the absence of a valid comparison group (n = 14), [1][2][3][7][8][9][10]12,13,20,25,26,28,35 the absence of a valid outcome variable (n = 4), 14,18,22,32 invalid study design (n = 2), 30,31 and redundant patient population (n = 1) (Fig. 1).…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-two articles were included in the final evidentiary table. Reasons for exclusion of fulltext articles included the absence of a valid comparison group (n = 14), [1][2][3][7][8][9][10]12,13,20,25,26,28,35 the absence of a valid outcome variable (n = 4), 14,18,22,32 invalid study design (n = 2), 30,31 and redundant patient population (n = 1) (Fig. 1).…”
Section: Search Resultsmentioning
confidence: 99%
“…The majority of excluded papers did not include a comparison group or control group. [1][2][3][7][8][9][10]12,13,20,25,26,28,35 Other reasons for exclusion included invalid study design (questionnaire survey), 30,31 redundant patient population 5 (only the paper with the longest reported follow-up was included), and absence of a valid outcome variable (change in ventricle size, development of spinal canal stenosis, historical description, and frequency of hospital visits). 14,18,22,32 Conclusions recommendation: There is insufficient evidence to demonstrate an advantage of one shunt hardware design over another for the treatment of pediatric hydrocephalus.…”
Section: Excluded Studiesmentioning
confidence: 99%
“…The death of 1 child was related to shunt malfunction. After a Another aspect is to compare our data with those of nonadjustable, gravity-assisted valves collected in a multicenter prospective study of 169 patients, including 86 infants (< 1 year) who received the paediGAV; 20 this study reported shunt survival rates of 65.6% and 57.4% and valve survival rates of 72.4% and 71.1% after 12 and 24 months, respectively. However, the comparison of a single-center retrospective study with a multicenter prospective study is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the feasibility of using this shunt system in an infant population is demonstrated, which has similarly been shown for a general pediatric population. 20,43,48 The use of the gravitational unit of the system to try to counteract severe overdrainage is also well tolerated by infants. Clinical observation has shown that during long-term follow-up, signs and symptoms of overdrainage (e.g., decreased ventricular size on imaging, diminished development of head circumference, and headaches) may develop with the advancing growth and activity of the child.…”
Section: Discussionmentioning
confidence: 99%
“…5,7,8,14 Gravitational valve systems compensate for increased pressure differences in the upright position and may therefore have a positive impact on symptoms related to overdrainage. 5,14 However, the use of a gravitational valve for relieving symptoms associated with overdrainage has not yet been addressed. The present study was designed to evaluate the effect of a gravitational valve system on the treatment of children with shunts and problems attributed to overdrainage.…”
Section: Discussionmentioning
confidence: 99%